2000
DOI: 10.1002/(sici)1098-2396(200001)35:1<45::aid-syn6>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual localization of neuropeptide FF receptors in the rat dorsal horn

Abstract: Although neuropeptide FF (NPFF) is generally considered an anti-opioid, its intrathecal administration produces analgesia. In the present study, the stable analog 1DMe ([D.Tyr(1), (NMe)Phe(3)]neuropeptide FF) was used in quantitative autoradiographic experiments in combination with surgical and chemical lesions to precisely localize NPFF receptors in the rat spinal cord. Ligation of lumbar dorsal spinal roots revealed the presence of NPFF receptors in dorsal root fibers and it induced a significant accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…NPFF2 is more ligand selective than NPFF1 [55]. RT-PCR, in situ hybridization and autoradiographic studies revealed the localization of both receptors in CNS areas implicated in pain transmission consistent with the supposed physiological role of NPFF peptides [44,46,[56][57][58][59][60][61]. The presence of two peptidergic systems of neurotransmission, mediated via two receptors (NPFF1 and NPFF2) stimulated by four or more peptides generated from pro-NPFFa and pro-NPFFb, respectively, may explain the complex pharmacological effects of NPFF-like peptides.…”
Section: Two Homologous Rf-amide Precursors: Pro-npffa and Pro-npffbsupporting
confidence: 62%
“…NPFF2 is more ligand selective than NPFF1 [55]. RT-PCR, in situ hybridization and autoradiographic studies revealed the localization of both receptors in CNS areas implicated in pain transmission consistent with the supposed physiological role of NPFF peptides [44,46,[56][57][58][59][60][61]. The presence of two peptidergic systems of neurotransmission, mediated via two receptors (NPFF1 and NPFF2) stimulated by four or more peptides generated from pro-NPFFa and pro-NPFFb, respectively, may explain the complex pharmacological effects of NPFF-like peptides.…”
Section: Two Homologous Rf-amide Precursors: Pro-npffa and Pro-npffbsupporting
confidence: 62%
“…General procedures were performed as detailed previously (Gouarderes et al, 2000;2001;. Brains and cervical spinal cords of wild-type (+/+/+; six animals) and homozygous (−/−/−; six animals) opioid-knockout mice killed by decapitation were removed rapidly, frozen in dry-ice-cooled 2-methylbutane (−45 • C) for 15-30 s, and kept at −80 • C. Rostrocaudal coronal sections (20 m thick) were cut at 140 m intervals throughout the nervous tissues (from forebrain to hindbrain regions and in cervical spinal cords) of animals in a cryostat microtome (Microm, France) at −17 • C, mounted on gelatin-chrome-alun-coated microscope slides and stored at −80 • C. Slide-mounted sections from +/+/+ and −/−/− mice were processed together in a paired protocol such that identical radioligand solutions for binding were used and apposition to the same phosphorscreen plate and parallel image analysis of brain sections from each genotype could be performed.…”
Section: Quantitative Receptor Autoradiographymentioning
confidence: 99%
“…In contrast, the NPFF R2 mRNA is relatively abundant in DRG and trigeminal ganglia (Bonini et al, 2000) though the highest levels are in the spinal cord. In the rat, ligation of lumbar dorsal spinal roots induced a significant accumulation of NPFF binding sites on the side peripheral to the ligature suggesting the axonal transport of NPFF binding sites, synthesized in DRG, towards primary afferent endings (Gouarderes et al, 2000). This migration of NPFF binding sites (receptor protein) was further supported by the finding of relatively dense NPFF binding sites in the spinal trigeminal tract (Allard et al, 1992;Dupouy and Zajac, 1996) where NPFF receptor mRNA was not detected (Liu et al, 2001).…”
Section: Distribution Of Npff and Npff Receptorsmentioning
confidence: 87%